The radiography students' perspective of the impact of COVID-19 on education and training internationally: a across sectional survey of the UK Devolved Nations (UKDN) and the United Arab Emirates (UAE). (October 2022) - Elshami, W.; Abuzaid, M.M.; McConnell, J.; Stewart, S.; Floyd, M.; Hughes, D.; McClintick, C.; Eckloff, K.; Leishman, L.; McFadden, S.
Abstract: Introduction: The overnight change in hospital practice and service delivery during the COVID-19 pandemic raises the question whether undergraduate radiography students received an adequate clinical experience. Many students had their clinical placements cancelled, deferred or replaced with simulated learning. As a way of dealing with the pandemic some hospitals were dedicated to COVID-19 patients only resulting in many elective procedures being cancelled. Many patients also chose to stay away from the hospital out of fear of infection or the desire to reduce the burden on staff. This resulted in a limited range of examinations and clinical experience for those students who were able to complete their clinical placement. Aim: This study aims to investigate the impact of COVID-19 on the education and training of radiography students internationally in the United Kingdom Devolved Nations (UKDN) and the United Arab Emirates (UAE), to determine any possible impact on their future careers. Method: Ethical permission was sought and granted from the Research Ethics Committees (ID: 21-04-12-02 and ID:21/0032). An online survey was developed using Google Forms and link was shared with students via email. Results: 262 students participated in the study [UAE (n = 60, 23%) and UKDN (n = 202, 77%)]. 72% stated that their clinical skills have improved and 82% were confident in the choice of radiography as a career. Participants from UAE displayed a higher tendency towards anxiety (p = 0.009). Students who were on clinical placements during the COVID-19 pandemic and worked with COVID-19 positive patients displayed less ongoing concern relating to COVID-19 (p = 0.004). 78% of the participants did not require wellbeing advice or request any type of wellbeing support from the higher education institutions (HEIs). Nevertheless, the study found that wellbeing of students was found to be negatively affected during the pandemic. Conclusion: Completing clinical placement during the COVID-19 pandemic allowed the continuation of education as students were allowed to improve their skills, confidence and resilience in coping with uncertainties and challenges. Undergraduate students should not be excluded from the clinical department during subsequent waves of COVID-19 or future pandemics to ensure continued workforce planning is possible. Implications for practice: HEIs should find solutions to compensate students for the loss of practical experience and skills due to the decreased number of patients in some areas of radiography practice. Providing academic and career counselling can assist students achieve their professional objectives and decrease the risk of attrition and problems upon qualification.